Microelements in Dust in the Snow Cover: a Case Study of the Cities of Tyumen and Tobolsk - A. V. Zakharchenko; A. A. Tigeev (Лëд и снег)
Inhomogeneities of trace elements content in dust of snow cover were studied in two industrial Siberian cities Tobolsk and Tyumen. The clustering method was used, for which standardized values of the content of trace elements in the snow dust of both cities were used. Eight clusters have been identified, which were divided into two classes by location: Tyumen and Tobolsk. The classes were divided into groups: non-specific and specific ones, of which the two subgroups were distinguished: technogenic and natural. The average values of trace elements in nominal terms were calculated for each cluster. Clusters C1, C2, C4, C7, C8 are characterized by a high content of heavy metals V, Cr, Ni, Cu, Co, Zn, Cd, W, Pb. Background clusters C5 and C6 have a low content of trace elements. Specific technogenic C4 contains more copper than other clusters, and C2 contains more lead. Sources of the formation of technogenic clusters are emissions into the atmosphere of enterprises of the fuel and energy complex, foundry and machine-building industries, and transport. The heterogeneity of the content of microelements in the snow dust under background conditions is demonstrated. The microelements are divided into natural background (cluster C5) and the background with anthropogenic pollution with higher content of Ag and Sn (cluster C6). In urban conditions, a solid phase of snow with a low and minimal content of trace elements in dust (cluster C3) is formed. Increased content of Ni and a reduced content of Pb and Sc is noted in the C3 cluster relative to C5 щту. Using the Mann-Whitne test, it was revealed that the content of trace elements in snow dust within the cities Tyumen and Tobolsk are different for the following elements: Li, V, Cr, Cu, Zn, Ga, As, Rb, Sr, Y, Zr, Nb, Mo, Ag, Cd, Sb, Cs, Ba, Pb. Mean values in are higher than similar ones in Tyumen. The content of Zn, As, Rb, Sc elements in urban clusters differs by more than two times relative to the background ones. In the case of elements Sn, Cs, W, the content of them in the snow dust of Tyumen is higher than that of Tobolsk. The method of clustering makes possible to identify natural background values (C5) and to calculate more precise values of the coefficient Kc as well as to determine the index of the integral pollution. In Tobolsk, the index is indicative of high and dangerous level of pollution, especially in the zone of technogenic impact. The average level is typical for the city of Tyumen.